Momentum and its relationship to futsal league players - Ahmed Rabie Abdel Ali (Musamus Journal of Physical Education and Sport (MJPES), 2025)
The aim of this research is to explore the relationship between psychological momentum and the performance of futsal league players. The aim is to determine how psychological momentum affects individual and team performance, as well as how various psychological factors influence improved athletic performance. The methodology relied on a descriptive-analytical study design, using Vallerand’s Psychological Momentum (PM) questionnaires to assess players’ psychological momentum. The research population included all professional futsal players in the National League during the 2025 season . A stratified random sample of 150 players from 10 teams was selected. Data were collected through pre- and post-match questionnaires, in addition to performance statistics extracted from official sources. The results showed a strong positive relationship between psychological momentum and player performance, with higher psychological momentum significantly associated with scoring goals and assists. The results also showed that psychological momentum was higher before matches but decreased after the competition, reflecting the psychological pressures players experience during play. The study also revealed statistically significant differences in psychological momentum between teams. The study confirms that psychological momentum is a crucial factor in enhancing athletic performance. Therefore , coaches and sports specialists should develop training programs that enhance players’ psychological momentum, which contributes to improving their performance and achieving better results in competitions.